Should Sex Be Considered an Effect Modifier in the Evaluation of Influenza Vaccine Effectiveness?. (4th September 2018) - Chambers, Catharine; Skowronski, Danuta M; Rose, Caren; Serres, Gaston De; Winter, Anne-Luise; Dickinson, James A; Jassem, Agatha; Gubbay, Jonathan B; Fonseca, Kevin; Drews, Steven J; Charest, Hugues; Martineau, Christine; et al.
Abstract: We investigated sex as a potential modifier of influenza vaccine effectiveness (VE) between 2010–2011 and 2016–2017 in Canada. Overall VE was 49% (95% confidence interval [CI], 43% to 55%) for females and 38% (95% CI, 28% to 46%) for males (absolute difference [AD], 11%; P = .03). Sex differences were greatest for influenza A(H3N2) (AD, 17%; P = .07) and B(Victoria) (AD, 20%; P = .08) compared with A(H1N1)pdm09 (AD, 10%; P = .19) or B(Yamagata) (AD, –3%; P = .68). They were also more pronounced in older adults ≥50 years (AD, 19%; P = .03) compared with those <20 years (AD, 4%; P = .74) or 20–49 years (AD, –1%; P = .90) but with variation by subtype/lineage. More definitive investigations of VE by sex and age are warranted to elucidate these potential interactions.